AUTHENTIC TEXTS IN TEACHING READING: BRIDGING THE GAP BETWEEN CLASSROOM LEARNING AND REAL-WORLD LITERACY (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The main objective of this article is to highlight the importance and efficiency of authentic texts in teaching reading across diverse learner contexts. Authentic texts—materials created for genuine communicative purposes (e.g., newspapers, blogs, advertisements)—offer unmodified linguistic and cultural input, fostering engagement, critical thinking, and pragmatic competence. Having seen a systematic review of 30 empirical studies (2010–2024), we demonstrate that authentic texts significantly enhance motivation, cultural awareness, and real-world literacy skills compared to traditional pedagogical materials. Challenges include lexical complexity and scaffolding demands, yet these are addressable through strategic task design. We argue for the structured integration of authentic texts into reading curricula to prepare learners for functional literacy demands. In this article, the concept of authentic texts is explained.  Form 10 students are chosen as a sample population of this study and most students are inclined to understand authentic texts as reading passages easily and efficiently developing cultural awareness and motivation to further studying. The result of this study is expected to help teachers to teach reading using new teaching strategies which encourages their students to learn more and enhance their reading proficiency.